2010
DOI: 10.4103/0973-6131.66771
|View full text |Cite
|
Sign up to set email alerts
|

Meditation on OM: Relevance from ancient texts and contemporary science

Abstract: Background:In Indian scriptures the sacred syllable Om is the primordial sound from which all other sounds and creation emerge which signifies the Supreme Power.Aims:To explore the significance of the syllable OM from ancient texts and effects of OM meditation in contemporary science.Descriptions from ancient texts:The descriptions of Om have been taken from four Upanisads (Mundaka, Mandukya, Svetasvatara, and Katha), the Bhagvad Gita, and Patanjali’s Yoga Sutras.Scientific studies on Om:Autonomic and respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The practice of TM improves academic performance of university students (Kember, 1985). Scientific studies on Om or Pranava suggest that the mental repetition of Om results in a physiological state at one time characterized by reduced physiological alertness, increased sensitivity as well as synchronicity, as well as changes at specific levels along the auditory pathway suggestive of increased sensitivity to sensory transmission (Kumar, Nagendra, Manjunath, Naveen, & Telles, 2010). Omkar chanting significantly effects the concentration, memory and level of fatigue (Khawale, 2011).…”
Section: The Concept Of Meditationmentioning
confidence: 99%
“…The practice of TM improves academic performance of university students (Kember, 1985). Scientific studies on Om or Pranava suggest that the mental repetition of Om results in a physiological state at one time characterized by reduced physiological alertness, increased sensitivity as well as synchronicity, as well as changes at specific levels along the auditory pathway suggestive of increased sensitivity to sensory transmission (Kumar, Nagendra, Manjunath, Naveen, & Telles, 2010). Omkar chanting significantly effects the concentration, memory and level of fatigue (Khawale, 2011).…”
Section: The Concept Of Meditationmentioning
confidence: 99%
“…[13] To study the long-term effects of SKY on brain function, EEG changes were recorded among 19 SKY practitioners and compared with the EEG patterns of 16 participants who did not practise SKY, yoga, or meditation. Significant increases in beta activity were observed in the left frontal, occipital, and midline regions of the brain in the SKY practitioners, as compared to controls.…”
Section: Influence Of Sky On Physiological Functionsmentioning
confidence: 99%
“…It brings inspiration and intuition and leads to a beneficial state of mind (Gurjar & Ladhake, 2008;Kumar, Nagendra, Manjunath, Naveen, & Telles, 2010) and improves concentration ability (Rautela, 2012). Das and Anand (2012) based on galvanic skin response study reported that "OM" sound has inherent features which bring psycho-physiologic relaxation.…”
mentioning
confidence: 98%
“…Das and Anand (2012) based on galvanic skin response study reported that "OM" sound has inherent features which bring psycho-physiologic relaxation. In Yoga, the role of OM sound is considered as a soothing, relaxing and unbroken thought to meditate upon (Kumar et al, 2010). Neuroimaging study on chanting of "OM" sound suggests the involvement of limbic system such as left anterior cingular cortex (ACC) and amygdale (Kalyani et al, 2011).…”
mentioning
confidence: 99%